(untitled) (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Acute kidney injury following cardiac surgery in children is a relatively common phenomenon. The risk ranges from 15% to 64% with a mortality rate of 10% to 89% for those who need dialysis. Objective: To identify the occurrence of acute kidney injury following cardiac surgery in children, as well as its consequences and treatment options. Methods: This study was conducted in the pediatric cardiac recovery center at Bangladesh Shishu Hospital & Institute from January 2019 to December 2020. Using the KDIGO (kidney disease improving global outcome) criteria, 50 children having cardiac surgery were assessed for the occurrence of AKI. Children were divided into two groups. The AKI group consists of 20 patients, whereas the non-AKI group consists of 30 patients. Age, sex, cardiac illness, past operations, RACHS-1 (Risk adjustment for congenital Heart surgery) and pre and post-operative creatinine levels were noted. Fisher’s exact test was used to determine whether or not AKI was associated with categorical factors, while the Mann- Whitney U-test was used to see whether or not AKI was associated with continuous variables. Results: Mean age of study population was 4.50±4.03 years for those who did not develop AKI and 7.55±5.79 years for those who did. Male constituted a majority in both groups. Despite the fact that patients with AKI were more acidotic at baseline, lower bicarbonate levels were not linked to an increased risk of AKI (p=0.89). Neither group had higher or lower pressure than the other. Time spent in bypass and crossclamping was comparable across AKI and non-AKI patients. Patients with AKI did not have a higher risk of developing extracellular fluid excess than non-AKI patients. There was no significant difference between the groups in terms of the average time spent on mechanical ventilation or total hospital stay in days (p=0.17 and p=0.62, respectively). Duration of stay in the cardiac recovery increased for patients who had AKI (p=0.02). The mortality rate among the AKI patients was 20% (4/14). In the control group without AKI, there was one death (3.33%) (p 0.0001). Conclusion: AKI is common complication of paediatric cardiac surgery. Prolong times spent on mechanical ventilation in the ICU and in the hospital have all been linked to AKI. DS (Child) H J 2021; 38(1): 44-48